2022
DOI: 10.4102/jamba.v14i1.1302
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability, impact and adaptation strategies of female farmers to climate variability

Abstract: In Africa, agriculture, particularly crop production, is a vital livelihood practice for women, who provide a larger proportion of the labour force. However, the high reliance on rain-fed agriculture, coupled with other socio-economic constraints, exposes female farmers to climatic risks. This paper investigates the participation of women in crop production, key challenges and their coping strategies for climatic disturbances. Drawing on the experiences of female farmers of Thaba Chweu Local Municipality (TCLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In this study, modern climate adaptation will refer to the use of inorganic fertilizer, drought-resistance seeds, pesticides, herbicides, and the use of irrigation. Dibakoane et al (2022) study found that most female farmers do not use modern agricultural coping strategies in Mpumalanga due to a lack of financial resources. The use of modern climate change adaptation becomes crucial when targeting formal markets, however, this requires financing.…”
Section: Introductionmentioning
confidence: 95%
“…In this study, modern climate adaptation will refer to the use of inorganic fertilizer, drought-resistance seeds, pesticides, herbicides, and the use of irrigation. Dibakoane et al (2022) study found that most female farmers do not use modern agricultural coping strategies in Mpumalanga due to a lack of financial resources. The use of modern climate change adaptation becomes crucial when targeting formal markets, however, this requires financing.…”
Section: Introductionmentioning
confidence: 95%
“…According to Addaney et al (2021), female farmers have displayed remarkable resilience to climate change by finding innovative ways to overcome these obstacles and increase their productivity. Another study revealed that most female farmers are farming grains (maize), which helps them improve food security in their households (Dibakoane et al, 2022). The study was anchored by the increasing demand for maize and cash crops due to the rising global population.…”
Section: Introductionmentioning
confidence: 99%
“…We know that risk is understood and experienced differently depending on context and identity, and this collection captures the diversity of perspectives that need to be considered; from people with disabilities (Ssennoga et al 2022 ), to pastoral households (Abrham & Mekuyie 2022 ), and farmers (Dibakoane, Siyongwana & Shabalala 2022 ; Matimolane et al 2022 ), to students (Kutywayo et al 2022 ), to families that include older people (Fatmah 2022 ). Various professionals also contribute to managing risk in society, and this is explored in relation to educators (Dzvimbo et al 2022 ), social workers (Matlakala, Makhubele & Nyahunda 2022 ), librarians (Chisita & Ngulube 2022 ), first responders (O’Neil & Kruger 2022 ), and health care professionals (Capili et al 2022 ).…”
mentioning
confidence: 99%